2021
DOI: 10.7759/cureus.18032
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Eptinezumab Use in Migraine

Abstract: We present a review of the efficacy and safety profile of eptinezumab (also known by the brand name Vyepti), a calcitonin gene-related peptide (CGRP) monoclonal antibody (mAb) developed by Lundbeck Seattle BioPharmaceuticals, Inc., that received its first approval in the USA on 21 February 2020 for the preventive treatment of migraine in adults. It is administered by an intravenous infusion at a 100 mg dose every 3 months and shows no drug interactions.Studies have shown that eptinezumab is an effective preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…37,38 By reducing the number of CGRP receptor activation, the vasodilation and neurogenic inflammation process may also be reduced, which will then disrupts the pain impulse transmission to the brain and prevent migrainous pain. 39 The efficacy and safety of eptinezumab for migraine prevention was similar to the recently United States Food and Drug Administration (FDA)-approved drug for preventive treatment of episodic migraine, atogepant. Results from recent meta-analysis study showed that 10 and 30 mg of atogepant treatment was associated with reduction in mean migraine days from baseline to 12-week treatment without increasing the incidence of AEs, and therefore, is considered effective and well-tolerated for prevention of episodic migraine in adults.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…37,38 By reducing the number of CGRP receptor activation, the vasodilation and neurogenic inflammation process may also be reduced, which will then disrupts the pain impulse transmission to the brain and prevent migrainous pain. 39 The efficacy and safety of eptinezumab for migraine prevention was similar to the recently United States Food and Drug Administration (FDA)-approved drug for preventive treatment of episodic migraine, atogepant. Results from recent meta-analysis study showed that 10 and 30 mg of atogepant treatment was associated with reduction in mean migraine days from baseline to 12-week treatment without increasing the incidence of AEs, and therefore, is considered effective and well-tolerated for prevention of episodic migraine in adults.…”
Section: Discussionmentioning
confidence: 81%
“…It works by binding the free CGRP peptide, therefore, preventing the interaction between CGRP and its receptor 37,38 . By reducing the number of CGRP receptor activation, the vasodilation and neurogenic inflammation process may also be reduced, which will then disrupts the pain impulse transmission to the brain and prevent migrainous pain 39 …”
Section: Discussionmentioning
confidence: 99%
“…Five patients (3.9%) experienced a serious AE (only one was considered related to eptinezumab), and the rate of study-drug discontinuation due to AEs was 6.3%. Several on-going studies are assessing eptinezumab in pediatric populations (NCT04537429 and NCT04965675), and RWD are still being collected [ 88 ].…”
Section: Calcitonin Gene-related Peptide (Cgrp)-targeted Mabsmentioning
confidence: 99%
“…71 In adults, antagonism of the CGRP pathway is associated with diminished headache days and medication usage. 72 Monoclonal antibodies (mAbs) to CGRP or its receptor-which require subcutaneous (erenumab, galcanezumab, fremanezumab) or intravenous administration (eptinezumab)-have shown safety and efficacy in trials of adults with migraine, [73][74][75][76][77] some with open-label data for 1 to 5 years. 78,79 To date, there are no published placebo-controlled trials of mAbs in children and adolescents with migraine.…”
Section: Novel Therapeutics Undergoing Evaluation In Children and Ado...mentioning
confidence: 99%